Pendampingan Pembelajaran Bahasa Arab dalam Rangka Meningkatkan Penguasaan Kosakata Bahasa Arab dan Penggunaannya di Pesantren DDI Mattoangin, Bantaeng - Hakim, Azizul; Garancang, Sabaruddin; Rappe; Jamaluddin (Faculty of Tarbiyah and Teacher Training, 2026)
The majority of Indonesian society adheres to Islam, with the Qur’an and the Sunnah serving as the main sources of guidance in daily life. Understanding these two sources requires proficiency in the Arabic language. However, not all Islamic educational institutions have an active Arabic-speaking environment. This community service program was conducted at Pesantren DDI Mattoangin Bantaeng and involved 30 participants consisting of male and female students. The program aimed to support Arabic language learning in order to improve students’ vocabulary mastery and their ability to use Arabic in daily communication. The activities were implemented through a direct mentoring approach packaged in the form of an Arabic Language Village, a learning model that had never been applied in the pesantren before. The results indicate significant improvements in daily vocabulary acquisition, pronunciation fluency, and speaking confidence, as reflected in increased student participation in dialogues, competitions, group conversations, and the use of Arabic within the dormitory environment. The program also had a positive impact on students’ motivation and attitudes toward learning Arabic. Therefore, this Arabic language mentoring program proved effective in creating an active and communicative language environment and is worthy of being developed sustainably to support the improvement of students’ Arabic language competence in the future.